Incentives to innovate under emission taxes and tradeable permits - Requate, Tilman (European journal of political economy, 1998)
I consider a competitive industry with constant returns to scale and pollution. Pollution control is implemented by either charging an effluent tax, or by auctioning off tradeable permits. The paper investigates the incentive to introduce a cleaner technology under either policy. In contrast to former research this model pays explicit attention to the final output market, finding that it depends crucially on the parameters whether permits or taxes provide a stronger incentive to innovate. Moreover we find that under taxes welfare may go down if a new technology is introduced whereas this can never happen under permits.
Gesehen am 08.08.2024